Predictive Value of 5-Methoxytryptophan on Clinical Outcome in Patients with Sepsis Associated Acute Kidney Injury - Sun X; Liu Y; Liu Y; Ai S; Luo P (Journal of Inflammation Research)
Xue Sun,1– 3 Yang Liu,4 Yan Liu,5 Shaozheng Ai,1– 3 Pengli Luo1,2 1Department of Nephrology, Affiliated Hospital of Qinghai University, Xining, 810000, People’s Republic of China; 2Clinical Research Center for Chronic Kidney Disease in Qinghai Province, Xining, 810000, People’s Republic of China; 3Research Center for High Altitude Medicine, Key Laboratory of High Altitude Medicine(Ministry of Education), Key Laboratory of Application and Foundation for High Altitude Medicine Research in Qinghai Province (Qinghai-Utah Joint Research Key Laboratory for High Altitude Medicine), Qinghai University, Xining, 810000, People’s Republic of China; 4Department of Chest Surgery, Affiliated Hospital of Qinghai University, Xining, 810000, People’s Republic of China; 5Department of Public Health, Qinghai University Medical College, Xining, 810000, People’s Republic of ChinaCorrespondence: Pengli Luo, The Affiliated Hospital of Qinghai University, No. 29 Tongren Road, Xining City, 810000, People’s Republic of China, Tel +8615297093191, Email qhlpl2108@163.comPurpose: Our study aims to investigate specific changes in serological 5-MTP expression in sepsis-associated acute kidney injury (SA-AKI) patients and assess its potential as a biomarker for SA-AKI occurrence. Additionally, we seek to evaluate the predictive value of 5-MTP in long-term clinical prognosis following SA-AKI.Patients and Methods: A prospective cohort study included 31 healthy controls and 78 patients diagnosed with sepsis at the Affiliated Hospital of Qinghai University. Following the collection of serological samples, 5-MTP levels were determined using targeted metabolomics.Additionally, we collected clinical data, including blood routine, biochemical, inflammatory indicators and severity of disease. Spearman correlation, COX regression analysis and Kaplan-Meier curves were used to evaluate the correlation between serum 5-MTP and renal function and the value of prognosis.Results: The findings revealed that serum 5-MTP levels were significantly elevated in SA-AKI patients compared to both the healthy control and sepsis groups(P< 0.05), and were associated with Scr, BUN, and eGFR levels(P< 0.05). Additionally, 5-MTP was identified as an independent influencing factor for all-cause mortality in patients with sepsis and SA-AKI. Higher levels of 5-MTP were linked to faster recovery of kidney function, while lower levels were associated with increased 90-day all-cause mortality in SA-AKI patients.Conclusion: 5-MTP may have a protective role in the development of SA-AKI, and an early increase in serological expression of 5-MTP could positively impact the prognosis of sepsis and SA-AKI.Keywords: sepsis associated acute kidney injury1, 5-methoxytryptophan2, prognosis3, 90-day mortality rate4, biomarker5